Georgia Architectural and Historic Properties Survey of Depot Street, Rebecca, Turner County, Ga., March 1981 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Depot Street, Rebecca, Turner County, Ga., March 1981. 5 identical 1 story rectangular shiplap sided house with gabled roof and exposed rafters. Double hung sash windows with 3/1 lights. Exterior chimney. Set on brick piers. Fair condition. Date of Construction: c. 1930. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough.
Georgia Architectural and Historic Properties Survey of Depot Street, Rebecca, Turner County, Ga., March 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 2 photographs. 2400 DPI TIF. 300 DPI 4x6 JPG. 92.3 MB (96,863,955 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Rebecca (Ga.); Turner County (Ga.)